Economically Dependent Self-Employment – Is it Time io Single out a New Title to Social Security? - Krajewski, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The foregoing study is an element of research conducted by the author as a part of the research project “In search of a legal model of self-employment in Poland. Comparative legal analysis.” In the article, the author analyses the legal position of the economically dependent self-employed people in Polish social security law. The main part of the considerations is the analysis of preferences granted to people conducting non-agricultural economic activity. The regulation in force in Spain is the author’s starting point for developing the concept of separating the economically dependent self-employed as an intermediate entity between those having a status of an employee and self-employed. In conclusion, the author presents the concept of introducing a separate title into the Act on the Social Insurance System – economically dependent self-employed.